2016
DOI: 10.1152/ajprenal.00517.2015
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of the xanthine oxidoreductase inhibitor topiroxostat on adenine-induced renal injury

Abstract: The aim of the present study was to reveal the effect of a xanthine oxidoreductase (XOR) inhibitor, topiroxostat (Top), compared with another inhibitor, febuxostat (Feb), in an adenine-induced renal injury model. We used human liver-type fatty acid-binding protein (L-FABP) chromosomal transgenic mice, and urinary L-FABP, a biomarker of tubulointerstitial damage, was used to evaluate tubulointerstitial damage. Male transgenic mice (n = 24) were fed a 0.2% (wt/wt) adenine-containing diet. Two weeks after the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Tissues fixed in methyl Carnoy's solution (60% methanol, 30% chloroform, and 10% glacial acetic acid) were embedded in paraffin. Serial sections (2‐μm thickness) were prepared for conventional histological assessment of Masson's trichrome staining, and for immunohistochemistry, and an indirect immunoperoxidase method was used to detect target antigens, as described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues fixed in methyl Carnoy's solution (60% methanol, 30% chloroform, and 10% glacial acetic acid) were embedded in paraffin. Serial sections (2‐μm thickness) were prepared for conventional histological assessment of Masson's trichrome staining, and for immunohistochemistry, and an indirect immunoperoxidase method was used to detect target antigens, as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Serial sections (2-μm thickness) were prepared for conventional histological assessment of Masson's trichrome staining, and for immunohistochemistry, and an indirect immunoperoxidase method was used to detect target antigens, as described previously. 17,20 Tissue fibrosis was defined as accumulation of extracellular matrix shown in blue in Masson's trichrome staining assessed at under ×100 magnification. Ten nonoverlapping fields from cortical and outer medullary areas were selected.…”
Section: Renal Histological and Immunohistological Analysismentioning
confidence: 99%
“…Previous studies demonstrated that topiroxostat reduced urinary albumin excretion in adenine‐induced kidney injury mice and in diabetic db/db mice (Kamijo‐Ikemori et al. ; Nakamura et al. ).…”
Section: Discussionmentioning
confidence: 95%
“…It was speculated that urinary L‐FABP increased with ROS, which was generated with activation of XO in renal tubule due to a decrease in mitochondrial ATP production function, promotion of ATP catabolism and increase hypoxanthine. In adenine‐induced renal injury model mice, topiroxostat treatment attenuated tubulointerstitial damage while decreasing albuminuria and avoiding increases in serum creatinine level . They also showed that mice treated with high doses of topiroxostat (3 mg/kg) had lower serum creatinine, urinary L‐FABP, and renal XOR than the mice group treated with febuxostat (3 mg/kg) .…”
Section: Discussionmentioning
confidence: 96%